Release of Two Orange-fleshed Sweetpotato Cultivars, ‘SPK004’ (‘Kakamega’) and ‘Ejumula’, in Uganda - Mwanga, R.O.M.; Odongo, B.; Niringiye, C.; Alajo, A.; Abidin, P.E.; Kapinga, R.; Tumwegamire, S.; Lemaga, B.; Nsumba, J.; Carey, E.E. (American Society for Horticultural Science, 2007)
Two orange-fleshed landrace sweetpotato [Ipomoea batatas L. (Lam.)] cultivars named ‘SPK004’ (‘Kakamega’) and ‘Ejumula’ were approved for release by the Ugandan Plant Variety Release Committee in Apr. 2004 (Mwanga et al., 2004a). This is the third lot of sweetpotato cultivars to be officially released by the sweetpotato program in Uganda, the first two being released in 1995 and 1999 (Mwanga et al., 2003). ‘Ejumula’ and ‘SPK004’ are Ugandan and Kenyan landrace germplasm, respectively, selected from a batch of 25 orange-fleshed sweetpotato (OFSP) clones of different origins (Table 1). Both cultivars have good storage root shapes if grown in light soils, high dry matter content, and excellent consumer acceptance, especially among children and women. The cultivars have low to moderate levels of field resistance to sweetpotato virus disease (SPVD) and Alternaria blight (Tables 2 and 3) and high storage root yields compared with the average national root yield of 4 t·ha−1 (International Potato Center, 1999). The release of these two cultivars provides consumers and farmers with high-quality sweetpotatoes of orange flesh for combating vitamin A deficiency in the country (Mwanga et al., 2004a, 2004b).